IN-HOSPITAL AND LATE OUTCOMES OF SURGICAL VERSUS ENDOVASCULAR REPAIR OF SEVERE AORTIC STENOSIS IN NEWBORNS AND INFANTS - Imanov, E.E.; Truba, Y.P.; Dziuryi, I.V.; Plyska, O.I.; Lazoryshynets, V.V.; Abdullayev, F.Z.; Shikhiyeva, L.S. (World of Medicine and Biology, 2025)
With the purpose to present in-hospital and late results of balloon aortic valvuloplasty versus surgical aortic valvotomy in newborns and infants with severe aortic valve stenosis 58 consecutive newborns and infants with severe aortic valve stenosis. 47 (81 %) patients underwent balloon aortic valvuloplasty (Group I); 11(19 %) patients – surgical aortic valvotomy (Group II) were enrolled. Initial aortic systolic pressure gradient in Group I comprised 67.6±19 mm Hg; in Group II – 69±23 mm Hg. Both groups were compared with regard to the persistence or recurrence of postoperative aortic pressure gradients, valve insufficiency and necessity for valve-related re-interventions. Late outcomes studied on 36 months. Following balloon aortic valvuloplasty and surgical aortic valvotomy procedures were revealed significant decline of aortic systolic pressure gradient, and increase of left ventricular ejection fraction in both groups. On 12 months following endovascular balloon aortic valvuloplasty aortic pressure gradient increased in most patients, and aortic insufficiency began to increase.
Keywords: aortic valve stenosis; surgical aortic valvulotomy; balloon valvuloplasty; infants